Design and implementation of static Huffman encoding hardware using a parallel shifting algorithm - Lee, Taeyeon; Park, Jaehong (IEEE transactions on nuclear science, 2004)
This work discusses the implementation of static Huffman encoding hardware for real-time lossless compression for the electromagnetic calorimeter in the CMS experiment. The construction of the Huffman encoding hardware illustrates the implementation for optimizing the logic size. The number of logic gates in the parallel shift operation required for the hardware was examined. The experiment with a simulated environment and an FPGA shows that the real-time constraint has been fulfilled and the design of the buffer length is appropriate.